Shrines and Pilgrimage in the Modern World New Itineraries into the Sacred - Margry, Peter Jan (Amsterdam University Press, 2008)
The modern pilgrimage - to sites ranging from Elvis's Graceland to the Vietnam veterans' annual Ride to the Wall to Jim Morrison's Paris grave - is intertwined with our existential uncertainties in the face of a rapidly changing world. In a climate that reproduces the religious quest in seemingly secular places, it is no longer clear exactly what the term pilgrimage infers - and this unique glimpse at the modern spiritual journeys critiques our notions of the secular and the sacred, while commenting on the media's multiplication of images that renders the modern pilgrimage a quest without an object. Using new ethnographical and theoretical approaches, this vivid collection offers a surprising new vision on the nonsecularity of the "secular" pilgrimage.